The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 5 Dinner — 12 to 1 p.m. 1½ tablespoonfuls per child of any of the following :— Meat, mince, stew, liver or brains, fish, sweetbreads, or cheese (grated), with vegetables or 3 tablespoonfuls vegetable broth cooked with milk. 1-2 heaped tablespoonfuls per child of boiled, mashed or jacket potatoes. 1-2 heaped tablespoonfuls per child of green vegetables, carrots, cauliflower, sprouts, peas, beans, spinach, or 1/2 to 1 tablespoonful of raw salad vegetables finely grated or chopped. 2-3 tablespoonfuls per child of milk pudding or milk blancmange, or steamed pudding or baked wheatmeal bread puddings with custard (1-2 heaped tablespoonfuls), for children of 15 months or more. Rusk or baked bread. Water to drink. Tea — 4.30 to 6 p.m. ⅓ pint milk. Wheatmeal bread or rusks, unsweetened biscuits or oatcakes, butter or margarine sandwiches with small quantities of finely shredded raw salads or vegetables, also seedless jam or grated carrot sprinkled with cocoa, small piece of plain cake (if available). Suggestions for sandwich fillings. Finely shredded lettuce, sprouts, cabbage, carrot, swede or beetroot, sliced tomato, grated carrot and cheese, and cocoa, jam, syrup, or dates, if available. APPENDIX I. MENUS. Although children do not need a great variety of food, 22 specimen individual daily menus are shown in Appendix I to give guidance and help. Recipes for 48 dishes are shown in Appendix II. Breakfast. Dinner. Tea. 1. ⅓ pt. Milk Fried Bacon and Fried Bread (1 oz. Bacon) Bread : Margarine Baked Mutton (1½oz,) Green Vegetable Potatoes Milk Pudding or Chocolate Junket ⅓pt. Milk (to complete the daily pint) Salad Sandwiches Plain Cake 2. ⅓ pt. Milk Porridge Toast: Margarine Stewed Fish Potatoes Mixed Root Vegetables Steamed Wheatmeal Bread Pudding ⅓ pt. Milk Carrot and Cocoa Sandwiches 3. ⅓ pt. Milk Minced Meat and Rice ⅓ pt. Milk Cereal Rusk Cheese and Lettuce in Wheatmeal Scones Toast: Margarine Potatoes Yeast Extract Green Vegetable Cress War and Peace Pudding 127/NU/5/5/1/28